Function of Internal Control in Financial Management in Pamona Puselemba District Poso - Abdul Pattawe; Muhammad Darma Halwi; Rahayu Indriasari; Jurana Jurana; Muhammad Ridwan Nasir (Sasambo: Jurnal Abdimas (Journal of Community Service), 2024)
This community service activity was carried out in the Pamona Puselemba sub-district, Poso. The partners for this activity are the heads and secretaries of villages in the Pamona Puselemba Poso sub-district. The aim of this service is to increase the capacity of village officials regarding the internal control function in financial management of Pamona Puselemba Poso District. Community service activities are carried out using the counseling method. The activity was attended by approximately 15 people consisting of village heads and secretaries in the Pamona Puselemba sub-district, Poso Regency. In the service program carried out in connection with counseling regarding the function of internal control in managing village finances in Pamona Puselemba District, Poso Regency, it turned out that it was able to improve the ability of village officials and officials in managing, using and being accountable for village funds in the villages of Pamona Puselemba District, Poso Regency. The results of this service activity are: first, increasing the ability of the community in the villages of Pamona Puselemba District, Poso Regency to play an active role and also be fully involved in the use of village funds in the form of village activities financed by the village fund budget; Second, increased accountability of village managers in Pamona Puselemba District, Poso Regency in being accountable for the use of village funds; Third, increasing communication and availability of information between the community and village officials in the management and use of village funds